Ajustes y reclasificaciones en auditoría financiera aplicados al componente documentos por cobrar a clientes. - Montalvan Zuñiga, Elizabeth Rosa (My University, 2017)
En el presente trabajo se resuelve la situación problemática que se le presenta al auditor al momento de efectuar correcciones a información financiera no razonable, utilizando ajustes y reclasificaciones a las partidas de estados financieros. Esto se presenta con un enfoque particular en la cuenta “Documentos por cobrar a clientes”, siendo ésta una partida contable que comprende los derechos representados por títulos comerciales de crédito a favor de la empresa, generados por las ventas a crédito efectuadas a los clientes; por lo tanto dicha cuenta cumple un papel de alta relevancia dentro de la información financiera. La metodología para el desarrollo de este informe se ejecuta en base a la consulta en artículos científicos para el marco conceptual de la investigación, aplicando el método descriptivo. Y como punto adicional, se efectúa el análisis de un caso práctico de auditaría financiera para una mayor comprensión del proceso de detección de riesgos y corrección de errores.
From a macro approach, the audit can be defined as an objective, systematic and profesional examination of various operations carried out by an entity. From this, the financial audit is born, as the process whose final result is the issuance of a report in which the auditor expresses his opinion on the financial situation of a company. One of the main objectives of the financial audit is to support the members of a company in the performance of their activities, providing analysis, evaluations, recommendations, advice and information. This paper addresses the problematic situation presented to the auditor when making corrections to unreasonable financial information, using adjustments and reclassifications to the financial statement items. This is presented with a particular focus on the "Receivables to customers" account, this being an accounting item that includes the rights represented by commercial credit certificates in favor of the company, generated by the sales to credit made to customers; Therefore, this account plays a highly relevant role in the financial information. The methodology for the development of this report is executed based on the consultation in scientific articles for the conceptual framework of the investigation, applying the descriptive method. And as an additional point, the analysis of a financial audit case is carried out for a better understanding of the process of risk detection and correction of errors.
Keywords: AUDITARÍA FINANCIERA; AJUSTES; RECLASIFICACIONES; DOCUMENTOS POR COBRAR; CONTROL INTERNO